Ophioviruses CPsV and MiLBVV movement protein is encoded in RNA 2 and interacts with the coat protein - Robles Luna, Gabriel (2013)
Citrus psorosis virus (CPsV) and Mirafiori lettuce big-vein virus (MiLBVV), members of the Ophioviridae family, have segmented negative-sense single-stranded RNA genomes. To date no reports have described how ophioviruses spread within host plants and/or the proteins involved in this process. Here we show that the 54K protein of CPsV is encoded by RNA 2 and describe its subcellular distribution. Upon transient expression in Nicotiana benthamiana epidermal cells the 54K protein, and also its 54K counterpart protein of MiLBVV, localize to plasmodesmata and enhance GFP cell-to-cell diffusion between cells. Both proteins, but not the coat proteins (CP) of the respective viruses, functionally trans-complement cell-to-cell movement-defective Potato virus X (PVX) and Tobacco mosaic virus (TMV) mutants. The 54K and 54K proteins interact with the virus-specific CP in the cytoplasm, suggesting a potential role of CP in ophiovirus movement. This is the first study characterizing the movement proteins (MP) of ophioviruses.